Penerapan Media Audio Visual Dalam Peningkatan Konsentrasi Belajar Pada Mata Pelajaran PAI Siswa Kelas 2 Di SD Negeri Wotbuwono - Fajriyah, Kuni; Fatimah, Siti; Rinawati, Atim (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the increase in students' concentration in participating in PAI learning in the second grade of SD Negeri Wotbuwono. This research is a class action research conducted for two cycles with students in each cycle twice meeting. Each cycle consists of stages of planning, implementation, observation, and reflection. The subject of the research in this study is the second grade students of SD Negeri Wotbuwono. The data collection technique uses tests, observations, and interviews. Data validity using triangulation. The results of the analysis show that learning in the first cycle as many as 48% of children have constituted participating in PAI learning. Meanwhile, in the second cycle, as many as 82% of children have concentrated on participating in PAI learning. So it can be concluded that there is an increase in student concentration in PAI learning through the application of audio visual media.